Tailoring D‐Amino Acid Oxidase from the Pig Kidney to R‐Stereoselective Amine Oxidase and its Use in the Deracemization of α‐Methylbenzylamine1. Issue 17 (18th March 2014) - Yasukawa, Kazuyuki; Nakano, Shogo; Asano, Yasuhisa
Abstract The deracemization of racemic amines to yield enantioenriched amines using S‐stereoselective amine oxidases (AOx) has recently been attracting attention. However, R‐stereoselective AOx that are suitable for deracemization have not yet been identified. An R‐stereoselective AOx was now evolved from porcine kidney D‐amino acid oxidase (pkDAO) and subsequently use for the deracemization of racemic amines. The engineered pkDAO, which was obtained by directed evolution, displayed a markedly changed substrate specificity towards R amines. The mutant enzyme exhibited a high preference towards the substrate α‐methylbenzylamine and was used to synthesize the S amine through deracemization. The findings of this study indicate that further investigations on the structure–activity relationship of AOx are warranted and also provide a new method for biotransformations in organic synthesis.